Éléments sur l'hydrologie de la partie atlasique de l'oued Guir (Maroc sud-oriental) et sur l'inondation catastrophique du 10 octobre 2008 - Ali Aït Hssaine (Physio-Géo)
In the upper catchment of the Guir wadi, the average annual rainfalls measured to Tazouguert, Kadoussa and Gourrama, between 1052 and 1360 m of height, do not reach 155 mm and the annual rainfalls rarely exceed 300 mm. At the heart of the Atlas massif (maximal height of the catchment 2736 m in the djebel Mesrouh), rainfalls are likely more abundant, but probably not much more. In spite of these low rainfalls, Guir sometimes witnesses violent floods. To Tazouguert (catchment of 2392 km2), from September, 1961 to August, 2007 (46 years of observation), the mean daily discharges exceeded 200 m3.s-1 during 9 years and maximum instantaneous discharges 1000 m3.s1 during 8 years. For these discharges, maximal values respectively reach 652 m3.s-1 on November 15th, 1993 and 3300 m3.s-1 on September 25th, 1962. Another major flood occurred on October 10th, 2008: mean daily discharge of 1397 m3.s-1 and peak flow of 3000 m3.s-1. The peak flows of September, 1962 and October, 2008 have a return period between 50 and 60 years. However the flood of October, 2008 was particularly violent upstream to the confluence with the Assefti wadi, the peak flow being estimated at 2260 m3.s-1 slightly upstream to Gourrama (for catchment of 286 km2). This flood caused catastrophic flooding in this sector. But the damages were higher than in September, 1962 until downstream of Tazouguert. The construction of dams is envisaged, in particular upstream to Tazouguert (El Gorane), but no major dam is planned on the high catchment.